1991
DOI: 10.1007/bf01316755
|View full text |Cite
|
Sign up to set email alerts
|

Latency and reactivation of infectious laryngotracheitis vaccine virus

Abstract: Latency and reactivation of a commercial infectious laryngotracheitis virus vaccine were demonstrated in live chickens. Virus was re-isolated at intervals between seven and fourteen weeks post-vaccination and this may be of epizootiological significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
0
7

Year Published

1999
1999
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(76 citation statements)
references
References 20 publications
(24 reference statements)
4
65
0
7
Order By: Relevance
“…In the first report, no differences were detectable between 7 field isolates made between 1979 and 1984 (Leib et al, 1986). In the second report, the vaccinal strain used in this study and a single field isolate made in 1979 were found to be similar in terms of clinical signs, acute phase shedding, latency and RFLP analysis (Hughes et al, 1991b). This led to the hypothesis that vaccine-derived virus is now established in the field, where it is responsible for many of the outbreaks.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In the first report, no differences were detectable between 7 field isolates made between 1979 and 1984 (Leib et al, 1986). In the second report, the vaccinal strain used in this study and a single field isolate made in 1979 were found to be similar in terms of clinical signs, acute phase shedding, latency and RFLP analysis (Hughes et al, 1991b). This led to the hypothesis that vaccine-derived virus is now established in the field, where it is responsible for many of the outbreaks.…”
Section: Discussionmentioning
confidence: 72%
“…Infection with both field and vaccinal strains of ILTV results in a carrier state characterized by latency in the trigeminal ganglia interspersed with brief periods of spontaneous virus shedding (Hughes et al, 1987;Hughes et al, 1991b;Williams et al, 1992). Natural stress factors including re-housing, mixing and the onset of lay are recognised factors that will trigger recrudescence and shedding of latent virus (Hughes et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical characteristics of the disease include decreased egg production, ill-thrift, oral and ocular discharge and conjunctivitis (Guy & Bagust, 2003). The disease is of economic importance as virulent strains can cause high levels of mortality and reduced productivity, while recovery from the disease can result in birds with a latent carrier status (Hughes et al ., 1987(Hughes et al ., , 1991b. Although strains may vary considerably in their virulence, there is recent evidence that vaccine-derived strains have become established in the field (Guy et al ., 1989;Graham et al ., 2000).…”
Section: Introductionmentioning
confidence: 99%
“…While it would have been of interest to examine the trigeminal nerve ganglia in these birds, it was not necessary for this study. Although latently infecting the trigeminal nerve, other herpesvirues can also be found in other tissues, e.g., infectious laryngotracheitis can also consistently infect the trachea 1,5,6 . This is consistent with the findings in this case where latently infected birds had virus in multiple tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The trigeminal nerve ganglia is commonly and latently infected by many herpesviruses in their respective hosts, including the infectious laryngotracheitis virus, one of the most closely related viruses to PsHV-1 and PsHV-2 5,6,15,18 . While it would have been of interest to examine the trigeminal nerve ganglia in these birds, it was not necessary for this study.…”
Section: Discussionmentioning
confidence: 99%